Irregular wave transmission on bottom bumps using fully nonlinear NURBS numerical wave tank. (September 2017) - Abbasnia, Arash; Ghiasi, Mahmoud; Abbasnia, Amir Hossein
Abstract: In this study, a fully nonlinear three-dimensional numerical wave tank (NWT) is developed to simulate propagation of nonlinear random sea wave over the bottom ripple patches. Evolution of the free surface is performed by the non-uniform rational B-spline formulation (NURBS) and the mixed Eulerian–Lagrangian method (MEL). A high-order boundary integral equation is used to solve the Laplace equation in the Eulerian frame. The free surface is updated by the material node method and the fourth-order Runge–Kutta time integration scheme. Appropriate numerical solutions are obtained by deploying damping zones at the both tank end walls. Also, the NURBS approximation is applied to compute the kinematics of the free surface particles. Propagation of the irregular waves in an NWT is conducted and compared with the available experimental and numerical data. Bragg reflection of the random sea wave due to bottom ripple patches are compared with the prior numerical studies. The fully nonlinear free surface evolution of transmitted spectrum due to presence of the hemispherical bumps is modeled successfully. Also fifth-order Stokes wave is applied as a strong nonlinear incident wave to interact with the hemispherical bottom bumps.